PERAN KELOMPOK TANI DALAM PENINGKATAN PENDAPATAN PETANI PADI SAWAH DI DESA ILOHELUMA KECAMATAN TILONGKABILA KABUPATEN BONE BOLANGO - Eka Mawarni; Mahludin Baruwadi; Irwan Bempah (Agrinesia: Jurnal Ilmiah Agribisnis, 2017)
This study aims to analyze: 1) To know the role of farmer groups in increasing the income of paddy farmers in Iloheluma Village, Tilongkabila District of Bone Bolango Regency, 2) To know the relationship between farmer group role in increasing farmer income in Iloheluma Village, Tilongkabila District, Bone Bolango Regency. This research was conducted in Iloheluma Kaecamatan Tilongkabila Village of Bone Bolango Regency from July to September of 2017. The method used is survey method that is data collection based on interview and observation. The sampling technique was done by using systematic sampling method. Namely sampling technique from a sequence of lists in a particular order where in this study population consists of 160 people and taken from multiples of 5 so that the results obtained as many as 32 people. Types and data sources used in this study are primary data and secondary data. Analysis of data used is Chi-Square analysis and farming by calculating cost, revenue, and income and determining relationship between farmer group role with farmer's income. The results showed that 1). Farmer groups in Iloheluma Village have roles that are group cooperation, seeking and disseminating information, group roles in planning management, cooperation of farmer group program implementation, and relationship with government institution and cooperative / KUD. 2) Test results show that count = 14.838 table = 9.49 so it can be concluded that rejected and accepted, which means there is a significant relationship between group cooperation (X) with farmer's income (Y).